Predictors of academic achievement of entering freshmen in UP in the Visayas High School - Nobleza, Abelardo
This study was conducted with the purpose of determining the best predictor, from among the variables considered, of academic achievement of the first year high school students of the University of the Philippines in the Visayas. The study was undertaken to confront probable predictors of academic achievement with statistical data gathered in a specific environment. However, less emphasis was given to confirming or refuting previous studies conducted on the same area. This view was maintained for the reason that academic achievement is a function of multi-factors such as: intellective, non-intellective, and intervening variables dependent upon a specific environment. To put the data in a nutsheel for better perusal and systematic summary of the derived numerical values, a general profile of the population was made. The degree of relationship and association between High School Grade Pint Average (HGPA) and the following variables: (1) Elementary Grade Point Average (EGPA), I. Q. Test (IQT), Achievement Test (AT), Annual Family Income (AFI), Educational Attainment of parents (EAP), and Sex was determined. Since the size of the correlation coefficient is an expression of the strength of the relationship, the variable with the highest obtained r when paired with HGPA answers the question -- What is the best predictor of academic achievement of the first year U.P.V. HighSchool Students? The population of this study were the students who completed first year high school during the academic years 1976-77, 1977-78, 1978-79, or a period of three years. The students with incomplete data and those who dropped before completing the first year were excluded. Of the 389 students officially enrolled during the reference period, 325, or 83.55 percent, were included in the study. Documentary analysis was used, employing both cross-section and time-series data to elicit more conclusive findings on the predictive value of variables considered in the study. To ascertain the sex difference in the academic achievement, the population was dichotomized into two according to sex. Throughout the study the relationship between the first year high school grade point average (HGPA) and the variables considered (except for sex) were computed, first by sex and then by year. The results f the study revealed that the achievement test has the highest obtained positive relationship when paired with HGPA with a range of .396 to .586 followed by the I.Q. Test with a range of .363 to .508. elementary grade point average .21 to .485, sex .047 to .254, educational attainment of parents .002 to .087 and annual family income - .267 to .259. Based on the above findings, there exists a very substantial relationship between the HGPA and the Achievement Test with the obtained r of .511 combining all the subjects within the period, significant at .01 level. This provides a substantial basis to conclude that the achievement test driven as an entrance examination to entering freshmen in U.P.V. High School is the best predictor of academic achievement. The obtained r between HGPA and Achievement test was used to derive an equation formula to predict the value of Y' (HGPA) from the knowledge of X' value (obtained score in achievement test). The predicted HGPA, therefore, of each student can be taken as the teacher's standard of expectation of the student' achievement in first year high school within acceptable limits. This study, therefore, recommends that: (1) The U.P. in the Visayas continue with the policy of selective admission of entering high school freshmen by using both the L. Padilla intelligence test and the U.P.V. achievement test supplemented by personal interview. (2). The following studies to be undertaken : a) A research to develop an instrument to measure the effect of peers on the academic achievement of students. b) A research similar to this one but extending the cross-section of the population to higher year levels (i.e., second year, third year, and fourth year). c) A research to find out whether the leadership manifested by students in school in both curricular activities is an indicator of academic achievement or a natural tendency of students who are scholastically achieving. d) A research on the effect on student achievement of student-teacher relationship. e) An investigation of the relationship between the HGPA and students' vocational interest. (3) In relation to vocational education, vocational and technical schools develop/improve instruments with which to screen prospective students, to predict their vocational and academic achievement.
Thesis (MA in Industrial Education). -- Manila : Technological University of the Philippines, 1980.